2015
DOI: 10.1044/2015_jslhr-l-14-0019
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Naming and Phonemic Awareness in Children With Reading Disabilities and/or Specific Language Impairment: Differentiating Processes?

Abstract: In studying RD and SLI, this research indicates that it is important to distinguish between RD-only, SLI-only, and comorbid groups. The comorbid group shows additive effects of both disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
0
23
0
1
Order By: Relevance
“…These studies have further provided clear evidence that children with SLI+DYS display deficits in phonological skills, using tasks measuring phonological awareness, nonword repetition, and rapid automatized naming (RAN), among others (Baird et al, 2011; Bishop et al, 2009; De Groot et al, 2015; Eisenmajer et al, 2005; Fraser et al, 2010; Kelso et al, 2007; McArthur & Castles, 2013; Ramus et al, 2013). However, the evidence remains somewhat mixed regarding the status of phonological processing skills for children with SLI-only.…”
Section: How Distinct Are Sli and Dyslexia?mentioning
confidence: 97%
See 2 more Smart Citations
“…These studies have further provided clear evidence that children with SLI+DYS display deficits in phonological skills, using tasks measuring phonological awareness, nonword repetition, and rapid automatized naming (RAN), among others (Baird et al, 2011; Bishop et al, 2009; De Groot et al, 2015; Eisenmajer et al, 2005; Fraser et al, 2010; Kelso et al, 2007; McArthur & Castles, 2013; Ramus et al, 2013). However, the evidence remains somewhat mixed regarding the status of phonological processing skills for children with SLI-only.…”
Section: How Distinct Are Sli and Dyslexia?mentioning
confidence: 97%
“…Subsequent studies have provided converging evidence for the existence of SLI+DYS and SLI-only subgroups (Baird, Slonims, Simonoff, & Dworzynski, 2011; Bishop, McDonald, Bird, & Hayiou-Thomas, 2009; De Groot, Van den Bos, Van der Meulen, & Minnaert, 2015; Eisenmajer, Ross, & Pratt, 2005; Fraser, Goswami, & Conti-Ramsden, 2010; Kelso, Fletcher, & Lee, 2007; McArthur & Castles, 2013; Ramus, Marshall, Rosen, & van der Lely, 2013). Most of the studies included participants with a wide range of chronological ages (e.g., 7–12 years or 6–16 years of age), and with the exception of Bishop et al (2009), all of these studies involved clinically-referred or convenience samples and only one assessment time point.…”
Section: How Distinct Are Sli and Dyslexia?mentioning
confidence: 98%
See 1 more Smart Citation
“…Some authors however suggested that different groups of poor readers can be distinguished among typically developing learners on the basis of their level of performance in reading (i.e. −2 vs. −1 standard deviation from the mean) and/or of associated features (i.e., poor readers showing a single PA or RAN deficit vs. those with a deficit in both PA and RAN; Cronin, 2013 ; de Groot et al, 2015 ). In fact, considerable inter-individual differences have been reported in skills associated with reading, such as PA, phonological short-term memory (PSTM), and RAN (Mann et al, 1989 ; Gathercole and Baddeley, 1993 ; Caravolas et al, 2001 ; Kirby et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the predictive relationship between RAN and reading fluency, it is not surprising that RAN shows good construct validity in terms of differentiating children with and without language learning impairments. In previous studies, children with dyslexia generally demonstrate RAN performance that is more than one standard deviation below the norm, and RAN has differentiated children with typical and atypical oral language development [27][28][29][30][31][32][33][34].…”
Section: Rapid Automatic Namingmentioning
confidence: 99%